Dynamic characteristics and fatigue life analysis of key parts of ring die pellet mill. (23rd March 2022) - Na, Risu; Li, Xin; Li, Shuai; Jia, Kaifa; Zhang, Weiguo
This paper establishes a drive system dynamic model of a ring die pellet mill, according to the working principle of the transmission system of the mill, Jeffcott rotor dynamics and mass concentration method. Modal analysis and numerical computation verified the accuracy of the dynamic model and key factors of the ring die pellet mill. In this study, random vibration analysis was performed based on the modal superposition by comparing the statistical tables of the failure data of the ring die pellet mill due to the short service life and severe wear of the ring die. In addition, combined with the material performance datebook, the Gaussian distribution and Miner's linear damage accumulation law were used to predict the ring die's fatigue damage and fatigue life.